Interrupted aza-Wittig reactions using iminophosphoranes to synthesize 11C–carbonyls. Issue 43 (4th May 2021) - Ismailani, Uzair S.; Munch, Maxime; Mair, Braeden A.; Rotstein, Benjamin H.
Abstract : Iminophosphoranes are coupled with CO2 and carbon-, nitrogen-, oxygen-, and sulfur-based nucleophiles to synthesize acyclic (radio)pharmaceuticals in high yield. Abstract : A direct CO2 -fixation methodology couples structurally diverse iminophosphoranes with various nucleophiles to synthesize ureas, carbamates, thiocarbamates, and amides, and is amenable for 11 C radiolabeling. This methodology is practical, as demonstrated by the synthesis of >35 products and isolation of the molecular imaging radiopharmaceuticals [ 11 C]URB694 and [ 11 C]glibenclamide.